2015
DOI: 10.11604/pamj.2015.22.243.7533
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of acute quadriceps tendon rupture (a case report with literature review)

Abstract: Quadriceps tendon rupture is uncommon and often overlooked in emergency. Tearing affects weakening tendon by systemic diseases or some medications. The mechanism is generally indirect. Inability to actively extend the knee associated to a supra-patellar defect evoke easily the diagnosis without other investigations. Surgical repair is realized in emergency to completely restore the extension. We report a case of a patient who has sustained of complete quadriceps tendon tear after a long period of tendon weaken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…[2] A wide variety of surgical treatments has been described, each with specific advantages and disadvantages. [3][4][5] For instance, the pull-out fixation has been performed the treatment of quadriceps tendon rupture, demonstrating satisfactory results. [1,6] Another technique based on fixation with suture anchors, has been widely reported as an effective method to repair a quadriceps tendon rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] A wide variety of surgical treatments has been described, each with specific advantages and disadvantages. [3][4][5] For instance, the pull-out fixation has been performed the treatment of quadriceps tendon rupture, demonstrating satisfactory results. [1,6] Another technique based on fixation with suture anchors, has been widely reported as an effective method to repair a quadriceps tendon rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in cases of missed or/and late diagnosis, tendon lengthening surgical repair with autograft, allograft and synthetic materials have been suggested for tendon reconstruction. [3] Transosseous repair has become the gold standard based on its association with improved long-term outcomes. [4,5] Most of the described techniques include passing the sutures through patellar tunnels, thus potentially increasing the risk of iatrogenic fracture of the patella and/or cartilage injury.…”
Section: Introductionmentioning
confidence: 99%
“…After the operation, walking was permitted albeit with a splint keeping the knee extended for 4 to 6 weeks, which helps protect the reconstruction that has been described [13]. Most authors have reported good functional results, always with complete motion recovery and return to previous activities [12,13]. a secondary rupture may occur but remains rarity [14].…”
Section: Discussionmentioning
confidence: 99%
“…After the operation, walking was permitted albeit with a splint keeping the knee extended for 4 to 6 wk, which helps protect the reconstruction[ 14 ]. A mobilization of 0°-30° can be allowed to prevent adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…A mobilization of 0°-30° can be allowed to prevent adhesions. Most authors have reported good functional results, always with complete motion recovery and return to previous activities[ 13 , 14 ]. Though quadriceps amyotrophy is quite common, it carries no functional repercussions in everyday life.…”
Section: Discussionmentioning
confidence: 99%